Motility and ultrastructure of large granular lymphocytes on lipid bilayers reconstituted with adhesion receptors LFA-1, ICAM-1, and two isoforms of LFA-3. - Carpén, O; Dustin, M; Springer, T; Swafford, J; Beckett, L; Caulfield, J (1991)
Large granular lymphocytes, mediators of NK activity, bind to other cells using both the LFA (lymphocyte function-associated)-1-ICAM and the CD2-LFA-3 adhesion pathways. Here we have studied the motility and ultrastructure of large granule lymphocyte (LGL) on lipid bilayers containing purified LFA-1, ICAM-1, and the transmembrane and glycophosphatidylinositol isoforms of LFA-3. LGLs moved at 8 microns/min on ICAM-1 but poorly (less than 1 microns/min) on its receptor pair LFA-1. TM-LFA-3 promoted locomotion at a rate close to ICAM-1, whereas the cells were less motile on GPI-LFA-3. The difference in the rates of locomotion on the two isoforms of LFA-3 is presumably attributable to their difference in anchoring and lateral mobility in the bilayer. In spite of the variation in motility the ultrastructure of the adhering cells was similar on all four ligands. LGLs contacted the membrane variably, i.e., cells adhering only in a few small areas or in larger areas were detected on each ligand. The relative percentage of the plasma membrane facing the lipid bilayer was greatest on ICAM-1 and least on the transmembrane isoform of LFA-3, demonstrating no correlation with motility. The ratio of adjacent plasma membrane to lipid bilayer was virtually constant for all four ligands. Activation of the LGLs with a combination of CD2 mAb T11(2) and T11(3) (T11(2/3) mAb) reduced the movement on ICAM-1 and virtually immobilized the cells on the other bilayers. In the presence of T11(2/3) mAb, the area of cell membrane attaching to bilayers containing ICAM-1 and GPI-LFA-3 was decreased and the percentage of plasma membrane facing other cells was increased. No preferential orientation of the Golgi apparatus or degranulation was detected in the absence or presence of T11(2/3) mAb, but a significantly lower percentage of LGLs on ICAM-1 contained a profile of the Golgi apparatus after exposure to T11(2/3) mAb. The results demonstrate that the motility of LGLs depends on the type of receptor in the opposing bilayer, the receptor mobility in the bilayer, and the activation of the cells. The ultrastructure of LGLs binding to any of the adhesion molecules does not have the characteristics of LGLs in cytolytic contact with target cells, suggesting that the mediation of an attack on a target requires more complex stimulus than any one of the single adhesion proteins tested here.